Positive plate, battery and electric device

By controlling the ratio of Mohs hardness level and compaction density in the positive electrode sheet, and combining the use of lithium manganese iron phosphate material and carbon cladding layer, the problem of structural instability of the positive electrode sheet after nano-native treatment is solved, and the battery cycle life is improved.

CN119905513APending Publication Date: 2025-04-29EVE POWER CO LTD

Patent Information

Application Number
CN202411975092.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

After nano-narcotic treatment, lithium manganese iron phosphate positive electrode sheets are prone to problems such as low compaction density, low peeling force, brittleness and easy to break and powder loss, which affects the cycle life of the lithium battery.

Method used

By controlling the ratio of the Mohs hardness level and compaction density of the positive electrode sheet within the range of 2.5≤H/PD≤4.5, combined with the use of lithium manganese iron phosphate material and carbon cladding, the comprehensive performance of the positive electrode sheet is improved.

Benefits of technology

It improves the structural stability of the positive electrode sheet, reduces material shedding and deformation, maintains appropriate internal stress, extends the service life of the positive electrode sheet, and thus improves the cycle life and stability of the battery.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a positive plate, a battery and a power utilization device, and belongs to the technical field of batteries, and the positive plate meets the formula: 2.5 < = H / PD < = 4.5; wherein H represents the Mohs hardness grade of the positive plate, and PD represents the compaction density of the positive plate. According to the positive plate provided by the embodiment of the invention, the structural stability can be ensured, the material falling and deformation conditions are reduced, the internal stress of the positive plate can be kept in a proper range, the cracking phenomenon of the positive plate is reduced, and the service life of the positive plate is prolonged. When the positive plate provided by the embodiment of the invention is applied to the battery, the cycle life and the stability of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet, a battery and an electrical device. Background Art

[0002] With the rapid development of new energy vehicles, the market scale continues to expand. As an important driving force for energy transformation, the new energy vehicle industry has broad development prospects.

[0003] As an important component of new energy vehicles, batteries have received extensive attention. In order to extend the service life of new energy vehicles, how to improve the cycle life of lithium batteries has become one of the most effective ways. Lithium batteries are mainly composed of pole pieces, diaphragms, electrolytes and shells. Among them, the positive pole piece is one of the important factors that determine the cycle life of lithium batteries. The purpose of improving the cycle life of batteries can be achieved by improving the performance of the positive pole piece.

[0004] As one of the main materials of lithium batteries, lithium iron manganese phosphate has always attracted much attention. However, due to its poor ionic conductivity, it needs to be nano-processed, which leads to problems such as low compaction density, low peeling force, brittleness and easy breakage, and powder loss in the positive electrode, affecting the cycle life of the battery. Summary of the invention

[0005] The embodiments of the present application provide a positive electrode sheet, a battery and an electric device. The positive electrode sheet can improve the overall performance of the positive electrode sheet and increase the cycle life of the battery by controlling the ratio of hardness to compaction density within a certain range.

[0006] In a first aspect, an embodiment of the present application provides a positive electrode sheet, and the positive electrode sheet satisfies the following formula: 2.5≤H / PD≤4.5;

[0007] Among them, H represents the Mohs hardness grade of the positive electrode sheet, and PD represents the compaction density of the positive electrode sheet.

[0008] In some embodiments, the positive electrode sheet satisfies the following formula: 3≤H / PD≤4.

[0009] In some embodiments, 7≤H≤9.

[0010] In some embodiments, 2.2 g / cm 3 ≤PD≤2.45g / cm 3 .

[0011] In some embodiments, 2.25 g / cm 3 ≤PD≤2.35g / cm 3 .

[0012] In some embodiments, the positive electrode sheet includes a positive electrode active material;

[0013] The positive electrode active material comprises a lithium manganese iron phosphate material and a carbon coating layer coated on the surface of the lithium manganese iron phosphate material.

[0014] In some embodiments, the positive electrode active material has a Mohs hardness rating of 0.5-2.5.

[0015] In some embodiments, the positive electrode active material has a Mohs hardness rating of 1-2.

[0016] In some embodiments, the thickness of the carbon coating layer is T, satisfying: 0.05 μm≤T≤0.1 μm.

[0017] In some embodiments, the material of the carbon coating layer includes at least one of conductive graphite, graphene, carbon nanotubes, and conductive carbon black.

[0018] In a second aspect, an embodiment of the present application provides a battery, comprising the positive electrode sheet as described above.

[0019] In some embodiments, a negative electrode sheet is also included;

[0020] The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes at least one of a graphite negative electrode material and a silicon-based negative electrode material.

[0021] In a third aspect, an embodiment of the present application provides an electrical device, comprising the battery as described above.

[0022] Beneficial effects of the embodiments of the present application:

[0023] In the positive electrode sheet provided in the embodiment of the present application, by making the Mohs hardness grade and compaction density of the positive electrode sheet meet 2.5≤H / PD≤4.5, the structural stability of the positive electrode sheet can be ensured, the material shedding and deformation in the positive electrode sheet can be reduced, and the internal stress of the positive electrode sheet can be kept within a suitable range, the cracking phenomenon of the positive electrode sheet can be reduced, and the service life of the positive electrode sheet can be extended. When the positive electrode sheet provided in the embodiment of the present application is applied to a battery, the cycle life and stability of the battery can be improved. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application. In addition, it should be understood that the specific embodiments described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0025] In a first aspect, an embodiment of the present application provides a positive electrode sheet, which satisfies the following formula: 2.5≤H / PD≤4.5, wherein H represents the Mohs hardness grade of the positive electrode sheet, and PD represents the compaction density of the positive electrode sheet.

[0026] In the positive electrode sheet provided in the embodiment of the present application, by making the Mohs hardness grade and compaction density of the positive electrode sheet meet 2.5≤H / PD≤4.5, the structural stability of the positive electrode sheet can be ensured, the material shedding and deformation in the positive electrode sheet can be reduced, and the internal stress of the positive electrode sheet can be kept within a suitable range, the cracking phenomenon of the positive electrode sheet can be reduced, and the service life of the positive electrode sheet can be extended. When the positive electrode sheet provided in the embodiment of the present application is applied to a battery, the cycle life and stability of the battery can be improved.

[0027] Among them, the hardness of the positive electrode sheet refers to its ability to resist external pressure or scratches, while the compaction density refers to the density of the positive electrode active material per unit volume. The Mohs hardness scale is a standard for measuring the hardness of minerals. Different substances are divided into different Mohs hardness scales based on the principle of whether one substance will be destroyed by another substance. It is understandable that the compaction density of the positive electrode sheet will affect its hardness. The higher the compaction density, the higher the hardness. However, when the compaction density is below a certain level, or when the compaction density is above a certain level, the hardness of the positive electrode sheet will not change with the change of the compaction density.

[0028] The positive electrode sheet provided in the embodiment of the present application satisfies the ratio of the mode hardness grade and the compaction density of the positive electrode sheet to 2.5≤H / PD≤4.5, which can ensure that the positive electrode sheet has a suitable hardness, so that the positive electrode sheet maintains good structural stability during the battery charging and discharging process, reduces the powdering and shedding of the material, and the deformation of the positive electrode sheet, and makes the positive electrode sheet have a suitable internal stress, reduces the cracking phenomenon, and prolongs the service life of the positive electrode sheet, thereby prolonging the cycle life of the battery. In addition, the compaction density and the mode hardness grade satisfy the above formula, which can also make the positive electrode sheet have good electron transmission performance, and improve the wetting performance of the electrolyte on the positive electrode sheet, so that the cycle life of the positive electrode sheet is improved. In other words, the embodiment of the present application can balance the physical properties and electrochemical properties of the positive electrode sheet by making the mode hardness grade and the compaction density of the positive electrode sheet satisfy the ratio of 2.5≤H / PD≤4.5, thereby ensuring the comprehensive performance of the positive electrode sheet, so that the positive electrode sheet can be used in the battery to help extend the battery cycle life.

[0029] It should be noted that the Mohs hardness grade of the positive electrode sheet can be tested with a Mohs hardness pen. The specific method is: hold the pen in writing mode, keep the Mohs hardness pen at an angle of about 70° to the positive electrode sheet to be tested, press the tip with a scale in the Mohs hardness pen and perform a scratch test on the surface of the positive electrode sheet to be tested, draw a straight line with a length of about 20 mm, observe the dents on the surface of the positive electrode sheet to be tested, and judge the Mohs hardness grade of the positive electrode sheet to be tested.

[0030] Illustratively, the ratio of the Mohs hardness rating to the compaction density of the positive electrode sheet may be 2.5, 3, 3.5, 4, or 4.5.

[0031] The method for testing the pattern hardness grade of the positive electrode sheet provided in the embodiments of the present application is for illustrative purposes only and is not intended to limit the scope of protection of the present application. Those skilled in the art may also adopt other testing methods.

[0032] In some embodiments, the positive electrode satisfies the following formula:

[0033] 3≤H / PD≤4.

[0034] By setting the ratio of the mode hardness grade and compaction density of the positive electrode sheet within the range of 3-4, the physical and electrochemical properties of the positive electrode sheet can be further balanced, while reducing material shedding, powdering and deformation in the positive electrode sheet, ensuring good electron transmission performance and electrolyte wetting performance of the positive electrode sheet, thereby extending the cycle life of the positive electrode sheet from multiple aspects and helping the cycle performance of the battery.

[0035] In some embodiments, 7≤H≤9. That is, the Mohs hardness level of the positive electrode sheet is between 7-9. When the Mohs hardness level of the positive electrode sheet is between 7-9, it can ensure that the positive electrode sheet has good structural stability, reduce the phenomena of material shedding and pulverization during the use of the positive electrode sheet, and the deformation of the positive electrode sheet. And in this range, the internal stress of the positive electrode sheet is small, which can reduce the problems of cracking and peeling of the positive electrode sheet caused by volume change. On the one hand, the problem of capacity reduction caused by material pulverization and shedding is reduced, and on the other hand, the cycle life of the battery is improved by improving the cycle stability of the positive electrode sheet.

[0036] Illustratively, the Mohs hardness rating of the positive electrode sheet may be 7, 7.5, 8, 8.5, or 9.

[0037] In some embodiments, 2.2 g / cm 3 ≤PD≤2.45g / cm 3 .

[0038] Compaction density is an important indicator to measure the density of the positive electrode sheet. It affects the energy density, charge and discharge performance and safety of the battery, and will also affect the conductivity and structural stability of the positive electrode sheet.

[0039] By setting the compaction density PD to 2.2 g / cm 3 -2.45g / cm 3, which can make the positive electrode sheet have more positive electrode active materials per unit volume, ensure higher energy density, and reduce problems such as cracking and peeling caused by excessive volume change, and ensure good electron transmission performance. In addition, when the compaction density is within the above range, the positive electrode sheet can have appropriate porosity, improve the degree of electrolyte infiltration into the positive electrode sheet, improve the utilization rate of positive electrode active materials, reduce the polarization phenomenon of the battery during charging and discharging, and improve the electrochemical performance and cycle life of the battery.

[0040] For example, the compaction density of the positive electrode sheet can be 2.2 g / cm 3 , 2.25g / cm 3 , 2.3g / cm 3 , 2.35g / cm 3 , 2.4g / cm 3 or 2.45g / cm 3 .

[0041] In some embodiments, 2.25 g / cm 3 ≤PD≤2.35g / cm 3 .

[0042] By setting the compaction density PD to 2.25 g / cm 3 -2.35g / cm 3 , which can enable the positive electrode to have both good electrochemical performance and cycle life.

[0043] It is understandable that the embodiment of the present application defines the ratio of the Mohs hardness grade and the compaction density in the positive electrode sheet. When the compaction density of the positive electrode sheet is set in the above range, the model hardness grade of the positive electrode sheet can also be within an appropriate range, thereby balancing the physical properties and electrochemical properties of the positive electrode sheet and extending the service life of the positive electrode sheet. When the positive electrode sheet provided in the embodiment of the present application is applied to a battery, the cycle life and stability of the battery can be improved.

[0044] In some embodiments, the positive electrode sheet includes a positive electrode active material, which includes a lithium manganese iron phosphate material and a carbon coating layer coated on the surface of the lithium manganese iron phosphate material.

[0045] That is to say, the positive electrode sheet provided in the embodiment of the present application adopts a positive electrode active material with a core-shell structure, wherein the core is lithium manganese iron phosphate material and the outer layer is coated with a carbon coating layer.

[0046] Lithium manganese iron phosphate has a high energy density. By using lithium manganese iron phosphate as the positive electrode active material, the energy density of the battery can be improved. Lithium manganese iron phosphate also has good low-temperature performance advantages. In addition, lithium manganese iron phosphate has an olivine structure, which is more stable during the charge and discharge process, and can ensure good safety and stability.

[0047] By providing a carbon coating layer on the lithium iron manganese phosphate material, a conductive carbon layer can be formed on the surface of the lithium iron manganese phosphate material, thereby improving the electronic conductivity of the positive electrode active material, helping to improve the charge and discharge performance of the battery, and reducing the internal resistance and charge and discharge polarization of the battery. The carbon coating layer can also provide protection for the lithium iron manganese phosphate material, reduce the corrosion of the lithium iron manganese phosphate material by harmful components in the electrolyte (such as hydrofluoric acid), and thus extend the cycle life of the battery. In addition, the carbon coating layer can also enhance the structural stability of the lithium iron manganese phosphate material and reduce problems such as shedding caused by volume expansion or contraction of the lithium iron manganese phosphate material during the charge and discharge process.

[0048] The carbon coating layer can be formed by chemical vapor deposition, atomic layer deposition, sol-gel method, co-precipitation method or sintering method.

[0049] In some embodiments, the positive electrode active material has a Mohs hardness rating of 0.5-2.5.

[0050] The positive electrode active material is an important component of the positive electrode sheet. The hardness of the positive electrode active material will have a great impact on the hardness and compaction density of the positive electrode sheet. By setting the Mohs hardness grade of the positive electrode active material to 0.5-2.5, it is helpful to control the Mohs hardness grade and compaction density of the positive electrode sheet within a suitable range, thereby meeting the requirement of 2.5≤H / PD≤4.5 in the positive electrode sheet and ensuring the cycle life of the positive electrode sheet.

[0051] Illustratively, the Mohs hardness rating of the positive electrode active material may be 0.5, 1, 1.5, 2, or 2.5.

[0052] The Mohs hardness level of the positive electrode active material is related to the material of the carbon coating layer on the one hand, and the preparation process on the other hand. For example, by selecting a material with a higher hardness level to coat the lithium manganese iron phosphate material, the Mohs hardness level of the positive electrode active material can be increased accordingly. By subjecting the positive electrode active material to high-temperature heat treatment, the Mohs hardness level of the positive electrode active material can also be changed.

[0053] In some embodiments, the positive electrode active material has a Mohs hardness rating of 1-2.

[0054] By setting the Mohs hardness level of the positive electrode active material to 1-2, it is helpful to control the Mohs hardness level and compaction density of the positive electrode sheet within an appropriate range, thereby meeting the requirement of 2.5≤H / PD≤4.5 in the positive electrode sheet and ensuring the cycle life of the positive electrode sheet. At the same time, the hardness of the positive electrode active material is mainly provided by the carbon coating layer. By setting the Mohs hardness level of the positive electrode active material to 1-2, the carbon coating layer can maintain a certain plastic deformation ability, reduce the problem of cracking of the positive electrode active material, maintain the integrity of the positive electrode active material, and ensure the protective effect of the carbon coating layer on the lithium manganese iron phosphate material, and ensure the stability of the positive electrode active material.

[0055] In some embodiments, the thickness of the carbon coating layer is T, satisfying: 0.05 μm≤T≤0.1 μm.

[0056] By setting the thickness of the carbon coating layer to be within the range of 0.05 μm-0.1 μm, the positive electrode active material can be guaranteed to have good ionic conductivity and help to maximize the capacity of the positive electrode active material. In addition, the carbon coating layer of appropriate thickness also helps to make the compaction density of the positive electrode sheet higher, and the compaction density of the positive electrode sheet can be adjusted as needed.

[0057] Exemplarily, the thickness of the carbon coating layer is 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm or 0.1 μm.

[0058] In some embodiments, the material of the carbon coating layer includes at least one of conductive graphite, graphene, carbon nanotubes, and conductive carbon black.

[0059] Among them, conductive graphite has high conductivity and stability. When used as a carbon coating layer of the positive electrode active material, it can form a conductive network on the surface of the lithium iron manganese phosphate material, thereby accelerating the electron transmission efficiency and improving the conductivity. The two-dimensional layered structure of graphene makes the transmission efficiency of electrons on its surface extremely high. When graphene is used as a carbon coating layer of the lithium iron manganese phosphate material, it can effectively improve the surface conductivity, improve the grain crystallinity of the lithium iron manganese phosphate material, and improve the electrochemical performance and cycle stability. In addition to having good conductivity, carbon nanotubes also have excellent mechanical strength and toughness. When used as a material for the carbon coating layer, they can not only improve the conductivity of the positive electrode active material, but also enhance the structural stability of the positive electrode active material, alleviate the volume change of the lithium iron manganese phosphate material during the charging and discharging process, reduce pulverization and shedding, and help extend the cycle life of the battery. Conductive carbon black can be evenly distributed on the surface of lithium iron manganese phosphate material to form a conductive network, which can improve the charge and discharge efficiency and rate performance of the battery. It can also reduce the side reaction between the lithium iron manganese phosphate material and the electrolyte, reduce the polarization of the battery, and effectively protect the lithium iron manganese phosphate material, thereby improving the cycle stability of the battery.

[0060] In a second aspect, an embodiment of the present application provides a battery, comprising the positive electrode sheet as described above.

[0061] The battery provided in the embodiment of the present application has all the beneficial effects of the above-mentioned positive electrode sheet, which will not be repeated here.

[0062] In some embodiments, the battery further comprises a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode active material, and the negative electrode active material comprises at least one of a graphite negative electrode material and a silicon-based negative electrode material.

[0063] Graphite negative electrode materials have a high specific surface area and good electrical conductivity, and can provide a high specific energy. Graphite negative electrode materials also have good chemical stability, can operate stably in the battery for a long time, are not prone to side reactions, and have a long cycle life. In addition, the preparation process of graphite negative electrode materials is relatively mature, and the production cost is low, which is conducive to reducing the overall cost of the battery.

[0064] The theoretical specific capacity of silicon-based negative electrode materials is much higher than that of graphite negative electrode materials, which can significantly increase the energy density of batteries. The working potential of silicon-based negative electrode materials is slightly higher than that of graphite, which can alleviate the problem of lithium decomposition and improve the safety performance of batteries.

[0065] In a third aspect, an embodiment of the present application provides an electrical device, comprising the battery as described above.

[0066] The electrical device provided in the embodiment of the present application has all the beneficial effects of the above-mentioned positive electrode sheet, which will not be described in detail here.

[0067] The following examples are further described in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples that do not specify specific conditions are usually based on the conditions recommended by the manufacturer.

[0068] Example 1

[0069] (1) coating a carbon coating layer on the surface of the lithium manganese iron phosphate material, and performing a high temperature heat treatment at 1600° C. to obtain a positive electrode active material; wherein the material of the carbon coating layer is conductive carbon black, the thickness of the carbon coating layer is 0.07 μm, and the Mohs hardness grade of the positive electrode active material is 2;

[0070] (2) The positive electrode active material, Super-P, SBR (styrene-butadiene rubber) and PVP (polyvinyl pyrrolidone) were mixed in a mass ratio of 96:2:1.5:0.5, added into N-methylpyrrolidone solvent, and stirred evenly to obtain a positive electrode slurry;

[0071] (3) The positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12 μm, and after drying and rolling, a positive electrode sheet is obtained; wherein the Mohs hardness grade of the positive electrode sheet is 8 and the compaction density is 2.3 g / cm 3 ;

[0072] (4) mixing graphite, conductive carbon black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 8:1:0.5:0.5, adding the mixture into deionized water, and mixing the mixture evenly to obtain a negative electrode slurry;

[0073] (5) The negative electrode slurry is evenly coated on a copper foil with a thickness of 5 μm, and after drying and rolling, a negative electrode sheet is obtained;

[0074] (6) Assembling the positive electrode sheet, the negative electrode sheet and the separator in the form of a stack, and then injecting the electrolyte, and obtaining a battery after formation and volume separation; wherein the separator is a 7+2+2 mixed coating separator, and the electrolyte contains a solvent and a lithium salt, the solvent is ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 30:5:25:40, and the lithium salt is 0.5 mol / L lithium bis(fluorosulfonyl)imide and 0.5 mol / L lithium hexafluorophosphate.

[0075] Example 2

[0076] (1) coating a carbon coating layer on the surface of the lithium manganese iron phosphate material, and performing a high temperature heat treatment at 1600° C. to obtain a positive electrode active material; wherein the material of the carbon coating layer is conductive carbon black, the thickness of the carbon coating layer is 0.07 μm, and the Mohs hardness grade of the positive electrode active material is 2;

[0077] (2) The positive electrode active material, Super-P, SBR and PVP were mixed in a mass ratio of 96:2:1.5:0.5, added into N-methylpyrrolidone solvent, and stirred evenly to obtain a positive electrode slurry;

[0078] (3) The positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12 μm, and after drying and rolling, a positive electrode sheet is obtained; wherein the Mohs hardness grade of the positive electrode sheet is 6, and the compaction density is 2.15 g / cm 3 ;

[0079] (4) mixing graphite, conductive carbon black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 8:1:0.5:0.5, adding the mixture into deionized water, and mixing the mixture evenly to obtain a negative electrode slurry;

[0080] (5) The negative electrode slurry is evenly coated on a copper foil with a thickness of 5 μm, and after drying and rolling, a negative electrode sheet is obtained;

[0081] (6) Assembling the positive electrode sheet, the negative electrode sheet and the separator in the form of a stack, and then injecting the electrolyte, and obtaining a battery after formation and volume separation; wherein the separator is a 7+2+2 mixed coating separator, and the electrolyte contains a solvent and a lithium salt, the solvent is ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 30:5:25:40, and the lithium salt is 0.5 mol / L lithium bis(fluorosulfonyl)imide and 0.5 mol / L lithium hexafluorophosphate.

[0082] Example 3

[0083] (1) coating a carbon coating layer on the surface of the lithium manganese iron phosphate material, and performing a high temperature heat treatment at 1600° C. to obtain a positive electrode active material; wherein the material of the carbon coating layer is conductive carbon black, the thickness of the carbon coating layer is 0.07 μm, and the Mohs hardness grade of the positive electrode active material is 2;

[0084] (2) The positive electrode active material, Super-P, SBR and PVP were mixed in a mass ratio of 96:2:1.5:0.5, added into N-methylpyrrolidone solvent, and stirred evenly to obtain a positive electrode slurry;

[0085] (3) The positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12 μm, and after drying and rolling, a positive electrode sheet is obtained; wherein the Mohs hardness grade of the positive electrode sheet is 9, and the compaction density is 2.4 g / cm 3 ;

[0086] (4) mixing graphite, conductive carbon black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 8:1:0.5:0.5, adding the mixture into deionized water, and mixing the mixture evenly to obtain a negative electrode slurry;

[0087] (5) The negative electrode slurry is evenly coated on a copper foil with a thickness of 5 μm, and after drying and rolling, a negative electrode sheet is obtained;

[0088] (6) Assembling the positive electrode sheet, the negative electrode sheet and the separator in the form of a stack, and then injecting the electrolyte, and obtaining a battery after formation and volume separation; wherein the separator is a 7+2+2 mixed coating separator, and the electrolyte contains a solvent and a lithium salt, the solvent is ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 30:5:25:40, and the lithium salt is 0.5 mol / L lithium bis(fluorosulfonyl)imide and 0.5 mol / L lithium hexafluorophosphate.

[0089] Example 4

[0090] (1) coating a carbon coating layer on the surface of the lithium manganese iron phosphate material, and performing a high temperature heat treatment at 1600° C. to obtain a positive electrode active material; wherein the material of the carbon coating layer is conductive carbon black, the thickness of the carbon coating layer is 0.15 μm, and the Mohs hardness grade of the positive electrode active material is 2;

[0091] (2) The positive electrode active material, Super-P, SBR and PVP were mixed in a mass ratio of 96:2:1.5:0.5, added into N-methylpyrrolidone solvent, and stirred evenly to obtain a positive electrode slurry;

[0092] (3) The positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12 μm, and after drying and rolling, a positive electrode sheet is obtained; wherein the Mohs hardness grade of the positive electrode sheet is 8 and the compaction density is 2.3 g / cm 3 ;

[0093] (4) mixing graphite, conductive carbon black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 8:1:0.5:0.5, adding the mixture into deionized water, and mixing the mixture evenly to obtain a negative electrode slurry;

[0094] (5) The negative electrode slurry is evenly coated on a copper foil with a thickness of 5 μm, and after drying and rolling, a negative electrode sheet is obtained;

[0095] (6) Assembling the positive electrode sheet, the negative electrode sheet and the separator in the form of a stack, and then injecting the electrolyte, and obtaining a battery after formation and volume separation; wherein the separator is a 7+2+2 mixed coating separator, and the electrolyte contains a solvent and a lithium salt, the solvent is ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 30:5:25:40, and the lithium salt is 0.5 mol / L lithium bis(fluorosulfonyl)imide and 0.5 mol / L lithium hexafluorophosphate.

[0096] Example 5

[0097] (1) coating a carbon coating layer on the surface of the lithium manganese iron phosphate material, and performing a high temperature heat treatment at 1000° C. to obtain a positive electrode active material; wherein the material of the carbon coating layer is conductive carbon black, the thickness of the carbon coating layer is 0.03 μm, and the Mohs hardness grade of the positive electrode active material is 1;

[0098] (2) The positive electrode active material, Super-P, SBR and PVP were mixed in a mass ratio of 96:2:1.5:0.5, added into N-methylpyrrolidone solvent, and stirred evenly to obtain a positive electrode slurry;

[0099] (3) The positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12 μm, and after drying and rolling, a positive electrode sheet is obtained; wherein the Mohs hardness grade of the positive electrode sheet is 8 and the compaction density is 2.3 g / cm 3 ;

[0100] (4) mixing graphite, conductive carbon black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 8:1:0.5:0.5, adding the mixture into deionized water, and mixing the mixture evenly to obtain a negative electrode slurry;

[0101] (5) The negative electrode slurry is evenly coated on a copper foil with a thickness of 5 μm, and after drying and rolling, a negative electrode sheet is obtained;

[0102] (6) Assembling the positive electrode sheet, the negative electrode sheet and the separator in the form of a stack, and then injecting the electrolyte, and obtaining a battery after formation and volume separation; wherein the separator is a 7+2+2 mixed coating separator, and the electrolyte contains a solvent and a lithium salt, the solvent is ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 30:5:25:40, and the lithium salt is 0.5 mol / L lithium bis(fluorosulfonyl)imide and 0.5 mol / L lithium hexafluorophosphate.

[0103] Example 6

[0104] (1) coating a carbon coating layer on the surface of the lithium manganese iron phosphate material, and performing a high temperature heat treatment at 1600° C. to obtain a positive electrode active material; wherein the material of the carbon coating layer is conductive carbon black, the thickness of the carbon coating layer is 0.07 μm, and the Mohs hardness grade of the positive electrode active material is 2;

[0105] (2) The positive electrode active material, Super-P, SBR and PVP were mixed in a mass ratio of 96:2:1.5:0.5, added into N-methylpyrrolidone solvent, and stirred evenly to obtain a positive electrode slurry;

[0106] (3) The positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12 μm, and after drying and rolling, a positive electrode sheet is obtained; wherein the Mohs hardness grade of the positive electrode sheet is 8 and the compaction density is 3.2 g / cm 3 ;

[0107] (4) mixing graphite, conductive carbon black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 8:1:0.5:0.5, adding the mixture into deionized water, and mixing the mixture evenly to obtain a negative electrode slurry;

[0108] (5) The negative electrode slurry is evenly coated on a copper foil with a thickness of 5 μm, and after drying and rolling, a negative electrode sheet is obtained;

[0109] (6) Assembling the positive electrode sheet, the negative electrode sheet and the separator in the form of a stack, and then injecting the electrolyte, and obtaining a battery after formation and volume separation; wherein the separator is a 7+2+2 mixed coating separator, and the electrolyte contains a solvent and a lithium salt, the solvent is ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 30:5:25:40, and the lithium salt is 0.5 mol / L lithium bis(fluorosulfonyl)imide and 0.5 mol / L lithium hexafluorophosphate.

[0110] Example 7

[0111] (1) coating a carbon coating layer on the surface of the lithium manganese iron phosphate material, and performing a high temperature heat treatment at 1600° C. to obtain a positive electrode active material; wherein the material of the carbon coating layer is conductive carbon black, the thickness of the carbon coating layer is 0.07 μm, and the Mohs hardness grade of the positive electrode active material is 2;

[0112] (2) The positive electrode active material, Super-P, SBR and PVP were mixed in a mass ratio of 96:2:1.5:0.5, added into N-methylpyrrolidone solvent, and stirred evenly to obtain a positive electrode slurry;

[0113] (3) The positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12 μm, and after drying and rolling, a positive electrode sheet is obtained; wherein the Mohs hardness grade of the positive electrode sheet is 9 and the compaction density is 2 g / cm 3 ;

[0114] (4) mixing graphite, conductive carbon black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 8:1:0.5:0.5, adding the mixture into deionized water, and mixing the mixture evenly to obtain a negative electrode slurry;

[0115] (5) The negative electrode slurry is evenly coated on a copper foil with a thickness of 5 μm, and after drying and rolling, a negative electrode sheet is obtained;

[0116] (6) Assembling the positive electrode sheet, the negative electrode sheet and the separator in the form of a stack, and then injecting the electrolyte, and obtaining a battery after formation and volume separation; wherein the separator is a 7+2+2 mixed coating separator, and the electrolyte contains a solvent and a lithium salt, the solvent is ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 30:5:25:40, and the lithium salt is 0.5 mol / L lithium bis(fluorosulfonyl)imide and 0.5 mol / L lithium hexafluorophosphate.

[0117] Example 8

[0118] (1) coating a carbon coating layer on the surface of the lithium manganese iron phosphate material, and performing a high temperature heat treatment at 1600° C. to obtain a positive electrode active material; wherein the material of the carbon coating layer is conductive carbon black, the thickness of the carbon coating layer is 0.05 μm, and the Mohs hardness grade of the positive electrode active material is 2;

[0119] (2) The positive electrode active material, Super-P, SBR and PVP were mixed in a mass ratio of 96:2:1.5:0.5, added into N-methylpyrrolidone solvent, and stirred evenly to obtain a positive electrode slurry;

[0120] (3) The positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12 μm, and after drying and rolling, a positive electrode sheet is obtained; wherein the Mohs hardness grade of the positive electrode sheet is 8 and the compaction density is 2.3 g / cm 3 ;

[0121] (4) mixing graphite, conductive carbon black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 8:1:0.5:0.5, adding the mixture into deionized water, and mixing the mixture evenly to obtain a negative electrode slurry;

[0122] (5) The negative electrode slurry is evenly coated on a copper foil with a thickness of 5 μm, and after drying and rolling, a negative electrode sheet is obtained;

[0123] (6) Assembling the positive electrode sheet, the negative electrode sheet and the separator in the form of a stack, and then injecting the electrolyte, and obtaining a battery after formation and volume separation; wherein the separator is a 7+2+2 mixed coating separator, and the electrolyte contains a solvent and a lithium salt, the solvent is ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 30:5:25:40, and the lithium salt is 0.5 mol / L lithium bis(fluorosulfonyl)imide and 0.5 mol / L lithium hexafluorophosphate.

[0124] Example 9

[0125] (1) coating a carbon coating layer on the surface of the lithium manganese iron phosphate material, and performing a high temperature heat treatment at 1600° C. to obtain a positive electrode active material; wherein the material of the carbon coating layer is conductive carbon black, the thickness of the carbon coating layer is 0.1 μm, and the Mohs hardness grade of the positive electrode active material is 2;

[0126] (2) The positive electrode active material, Super-P, SBR and PVP were mixed in a mass ratio of 96:2:1.5:0.5, added into N-methylpyrrolidone solvent, and stirred evenly to obtain a positive electrode slurry;

[0127] (3) The positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12 μm, and after drying and rolling, a positive electrode sheet is obtained; wherein the Mohs hardness grade of the positive electrode sheet is 8 and the compaction density is 2.3 g / cm 3 ;

[0128] (4) mixing graphite, conductive carbon black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 8:1:0.5:0.5, adding the mixture into deionized water, and mixing the mixture evenly to obtain a negative electrode slurry;

[0129] (5) The negative electrode slurry is evenly coated on a copper foil with a thickness of 5 μm, and after drying and rolling, a negative electrode sheet is obtained;

[0130] (6) Assembling the positive electrode sheet, the negative electrode sheet and the separator in the form of a stack, and then injecting the electrolyte, and obtaining a battery after formation and volume separation; wherein the separator is a 7+2+2 mixed coating separator, and the electrolyte contains a solvent and a lithium salt, the solvent is ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 30:5:25:40, and the lithium salt is 0.5 mol / L lithium bis(fluorosulfonyl)imide and 0.5 mol / L lithium hexafluorophosphate.

[0131] Comparative Example 1

[0132] (1) coating a carbon coating layer on the surface of the lithium manganese iron phosphate material, and performing a high temperature heat treatment at 1600° C. to obtain a positive electrode active material; wherein the material of the carbon coating layer is conductive carbon black, the thickness of the carbon coating layer is 0.07 μm, and the Mohs hardness grade of the positive electrode active material is 2;

[0133] (2) The positive electrode active material, Super-P, SBR and PVP were mixed in a mass ratio of 96:2:1.5:0.5, added into N-methylpyrrolidone solvent, and stirred evenly to obtain a positive electrode slurry;

[0134] (3) The positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12 μm, and after drying and rolling, a positive electrode sheet is obtained; wherein the Mohs hardness grade of the positive electrode sheet is 8, and the compaction density is 3.6 g / cm 3 ;

[0135] (4) mixing graphite, conductive carbon black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 8:1:0.5:0.5, adding the mixture into deionized water, and mixing the mixture evenly to obtain a negative electrode slurry;

[0136] (5) The negative electrode slurry is evenly coated on a copper foil with a thickness of 5 μm, and after drying and rolling, a negative electrode sheet is obtained;

[0137] (6) Assembling the positive electrode sheet, the negative electrode sheet and the separator in the form of a stack, and then injecting the electrolyte, and obtaining a battery after formation and volume separation; wherein the separator is a 7+2+2 mixed coating separator, and the electrolyte contains a solvent and a lithium salt, the solvent is ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 30:5:25:40, and the lithium salt is 0.5 mol / L lithium bis(fluorosulfonyl)imide and 0.5 mol / L lithium hexafluorophosphate.

[0138] Comparative Example 2

[0139] (1) coating a carbon coating layer on the surface of the lithium manganese iron phosphate material, and performing a high temperature heat treatment at 1600° C. to obtain a positive electrode active material; wherein the material of the carbon coating layer is conductive carbon black, the thickness of the carbon coating layer is 0.07 μm, and the Mohs hardness grade of the positive electrode active material is 2;

[0140] (2) The positive electrode active material, Super-P, SBR and PVP were mixed in a mass ratio of 96:2:1.5:0.5, added into N-methylpyrrolidone solvent, and stirred evenly to obtain a positive electrode slurry;

[0141] (3) The positive electrode slurry is evenly coated on an aluminum foil with a thickness of 12 μm, and after drying and rolling, a positive electrode sheet is obtained; wherein the Mohs hardness grade of the positive electrode sheet is 9, and the compaction density is 1.9 g / cm 3 ;

[0142] (4) mixing graphite, conductive carbon black, carboxymethyl cellulose and styrene-butadiene rubber in a mass ratio of 8:1:0.5:0.5, adding the mixture into deionized water, and mixing the mixture evenly to obtain a negative electrode slurry;

[0143] (5) The negative electrode slurry is evenly coated on a copper foil with a thickness of 5 μm, and after drying and rolling, a negative electrode sheet is obtained;

[0144] (6) Assembling the positive electrode sheet, the negative electrode sheet and the separator in the form of a stack, and then injecting the electrolyte, and obtaining a battery after formation and volume separation; wherein the separator is a 7+2+2 mixed coating separator, and the electrolyte contains a solvent and a lithium salt, the solvent is ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 30:5:25:40, and the lithium salt is 0.5 mol / L lithium bis(fluorosulfonyl)imide and 0.5 mol / L lithium hexafluorophosphate.

[0145] The peel strength of the positive electrode sheets in Examples 1-9 and Comparative Examples 1-2, and the capacity retention rates of the batteries in Examples 1-9 and Comparative Examples 1-2 after 1000 cycles were tested.

[0146] The test method for peel strength is as follows: prepare a flat thin steel plate with a length of about 200-300mm and a width of about 40-60mm, and paste a double-sided tape with a length greater than the sample test length and the same width as the electrode in the center of the steel plate, smooth it with force to make it fit tightly, then remove the cover paper of the double-sided tape, paste the positive electrode on the tape, and ensure that the electrode and the tape are completely matched and fit; use a tensile machine and two clamps, insert the steel plate with the electrode pasted and fixed into the lower clamp to fix it vertically, and insert the unpainted electrode into the upper clamp, so that the electrode in the upper and lower clamps is fixed at 180° or 90°; use a tensile testing machine to continuously peel at a tensile speed of 100mm / min until the electrode and the foil are completely separated. The test result uses the average value of the stable stage as the peel strength value.

[0147] The test method for capacity retention is: fully charge and discharge the battery at 25°C, and record the cycle capacity retention rate after 1000 cycles. Full charge: charge at 0.33C constant current to a cut-off voltage of 4.2V, then change to constant voltage charging with a cut-off current of 0.05C. Full discharge: discharge at 0.33C to 2.5V. The results are shown in Table 1:

[0148] Table 1 Performance test results of different embodiments and comparative examples

[0149] Peel strength(N) Capacity retention rate (%) Example 1 0.23 93.9 Example 2 0.18 90.1 Example 3 0.21 91.5 Example 4 0.15 88.4 Example 5 0.11 85.7 Example 6 0.08 81.2 Example 7 0.31 84.9 Example 8 0.21 91.8 Example 9 0.27 92.5 Comparative Example 1 0.05 70.2 Comparative Example 2 0.35 75.7

[0150] As can be seen from Table 1, relative to Comparative Example 1, the peel strength of the positive electrode sheet and the capacity retention rate of the battery in Examples 1-9 of the present application are significantly improved, which is mainly because the Mohs hardness grade H and the compaction density of the positive electrode sheet in Examples 1-9 meet the requirements of 2.5≤H / PD≤4.5, ensuring the structural stability of the positive electrode sheet, reducing the material shedding and deformation in the positive electrode sheet, extending the service life of the positive electrode sheet, and thus improving the cycle performance of the battery. Relative to Comparative Example 2, the capacity retention rate of the battery in the embodiment of the present application is significantly improved, while the peel strength of the positive electrode sheet is reduced. This is mainly because the positive electrode sheet in Comparative Example 2 has a higher Mohs hardness grade, which improves the material bonding strength in the positive electrode sheet, so that the peel strength of the positive electrode sheet is improved, but due to its low compaction density, the positive electrode sheet material is pulverized and shed during the battery cycle, resulting in poor cycle performance.

[0151] From the comparison of Examples 1-9, it can be seen that when the Mohs hardness grade H and compaction density PD of the positive electrode sheet meet the following conditions: 7≤H≤9, 2.20 g / cm 3 ≤PD≤2.45g / cm 3 At the same time, the thickness T of the carbon coating layer in the positive electrode active material and the Mohs hardness grade meet the following conditions: 0.05 μm ≤ T ≤ 0.1 μm. When the Mohs hardness grade is 0.5-2.5, the peel strength of the positive electrode sheet and the capacity retention rate of the battery can be improved, thereby ensuring the comprehensive performance of the battery.

[0152] The embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet satisfies the following formula: 2.5≤H / PD≤4.5; Wherein, H represents the Mohs hardness grade of the positive electrode sheet, and PD represents the compaction density of the positive electrode sheet.

2. The positive electrode sheet according to claim 1, characterized in that: The positive electrode sheet satisfies the following formula: 3≤H / PD≤4.

3. The positive electrode sheet according to claim 1, characterized in that: 7≤H≤9。 4. The positive electrode sheet according to claim 1, characterized in that: 2.2g / cm 3 ≤PD≤2.45g / cm 3 。 5. The positive electrode sheet according to any one of claims 4, characterized in that: 2.25g / cm 3 ≤PD≤2.35g / cm 3 。 6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: including a positive electrode active material; The positive electrode active material includes a lithium manganese iron phosphate material and a carbon coating layer coated on the surface of the lithium manganese iron phosphate material.

7. The positive electrode sheet according to claim 6, characterized in that: The Mohs hardness rating of the positive electrode active material is 0.5-2.

5.

8. The positive electrode sheet according to claim 7, characterized in that: The Mohs hardness level of the positive electrode active material is 1-2.

9. The positive electrode sheet according to claim 6, characterized in that: The thickness of the carbon coating layer is T, which satisfies: 0.05 μm≤T≤0.1 μm.

10. The positive electrode sheet according to claim 6, characterized in that: The material of the carbon coating layer includes at least one of conductive graphite, graphene, carbon nanotubes and conductive carbon black.

11. A battery, characterized in that: Comprising the positive electrode sheet as described in any one of claims 1 to 10.

12. The battery according to claim 11, characterized in that Also includes a negative electrode sheet; The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes at least one of a graphite negative electrode material and a silicon-based negative electrode material.

13. An electrical device, characterized in that: Comprising a battery as claimed in claim 11 or 12.

Citation Information

Patent Citations

  • Lithium manganese iron phosphate composite material, preparation method thereof, positive electrode and lithium ion battery

    CN114655943A

  • Positive plate, preparation method thereof and secondary battery

    CN115472770A

  • Secondary battery and electric device

    CN118099396A

  • Sodium iron phosphate electrode material and preparation method thereof

    CN118610404A

  • Positive plate and lithium ion battery

    CN118943295A

Cited By

  • Negative plate and secondary battery thereof

    CN121922569A

  • Negative electrode sheet and secondary battery

    CN121922569B

  • Positive electrode sheet, battery, and electric device

    EP4797337A1

  • Positive electrode sheet, battery, and electric device

    WO2026143906A1